Formation of Anti-Reflection Coatings Based on Nanostructured Aluminum and Barium Titanate Xerogel Layer - S. K. Lazarouk; T. F. Raichenok; L. P. Tomashevich; E. I. Lashkovskaya; A. A. Povzhik; N. V. Gaponenko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2024)
The research has been carried out on the formation of anti-reflection coatings based on porous aluminum obtained by electrochemical anodic etching and a layer of barium titanate xerogel deposited on its surface. The  thickness of the porous aluminum ranged from 15 to 100 microns. Analysis of the reflection spectra of the resulting structures showed effective anti-reflection properties of the formed coatings with a specular reflection coefficient of 0.25–2.50 % in the range of 200–1100 nm. The use of formed coatings with a low reflectance coefficient is possible in aircraft manufacturing, electronics and energy.